2014
DOI: 10.1103/physrevlett.112.157402
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Thin Films in Lieu of Hyperbolic Metamaterials in the Near Field

Abstract: We show that the near-field functionality of hyperbolic metamaterials (HMM), typically proposed for increasing the photonic local density of states (LDOS), can be achieved with thin metal films. Although HMMs have an infinite density of internally propagating plane-wave states, the external coupling to nearby emitters is severely restricted. We show analytically that properly designed thin films, of thicknesses comparable to the metal size of a hyperbolic metamaterial, yield an LDOS as high as (if not higher t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 51 publications
10
65
0
Order By: Relevance
“…This observation is in general in agreement with a recent investigation of heat transfer between hyperbolic metamaterials, which showed that a single-layer structure could operate as well or better than hyperbolic metamaterials especially in the limit of small vacuum gap sizes [39]. With the gap sizes that we consider here, there can be significant contributions from both the multi-layers and the top surfaces.…”
Section: Hybrid Polaritons In Graphene/hbn Multilayerssupporting
confidence: 78%
“…This observation is in general in agreement with a recent investigation of heat transfer between hyperbolic metamaterials, which showed that a single-layer structure could operate as well or better than hyperbolic metamaterials especially in the limit of small vacuum gap sizes [39]. With the gap sizes that we consider here, there can be significant contributions from both the multi-layers and the top surfaces.…”
Section: Hybrid Polaritons In Graphene/hbn Multilayerssupporting
confidence: 78%
“…For d < 100 nm, the HTC of the single layer resembles that of the mHMM with SiC on top, and for d > 100 nm, it resembles the case of the mHMM with Ge on top. Therefore, the statement of [97] seems to be correct although in our plots the mHMM gives slightly larger results than the single-layer structure for d = 100 nm.…”
Section: K)mentioning
confidence: 79%
“…In addition, the result predicted by the EMT is plotted. even greater heat transfer" [97]. Therefore, we want to compare the sHTC and the HTC for our SiC/Ge mHMM structure with a structure consisting of a single 10-nm layer of SiC on a semi-infinite Ge substrate.…”
Section: K)mentioning
confidence: 99%
“…Recently, a number of works have demonstrated that near-field radiative heat transfer is enhanced by many orders of magnitude compared to the far-field limit for closely spaced objects with either natural 10,11 or engineered resonant surface modes [12][13][14][15][16] . There have also been efforts to couple these near-field modes into the far-field with the use of grating structures 17 , antennas 18 , and a thermal extraction lens 19,20 .…”
mentioning
confidence: 99%